The relationship between visfatin, resistin and CRP parameters and insulin resistance in obese and non-obese type 2 diabetic individuals - Yüksel, Arzu; Telci, Ayşe Gül Sündüs; Kubat Üzüm, Ayşe (The European Research Journal, 2025)
Objectives: Inflammation caused by adipokines such as adiponectin, leptin, resistin, visfatin, interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) released by fat cells and immune cells within fat tissue is a significant factor in the onset of insulin resistance and Type 2 diabetes mellitus (T2DM). This study explores the relationship among these adipokines and insulin resistance in T2DM patients, focusing on the impact of abdominal obesity. Methods: The study involved 73 adult T2DM patients who were seperated into two groups based on their body mass index (BMI): 47 were classified as obese (BMI ≥30 kg/m²), and 26 were classified as non-obese (BMI